A HOME-BASED PREHABILITATION PROGRAM, DELIVERED THROUGH AN INTERNET-BASED PLATFORM, IN PATIENTS WITH LOCALLY ADVANCED GASTROESOPHAGEAL JUNCTION AND STOMACH ADENOCARCINOMA, UNDERGOING PERIOPERATIVE CHEMOTHERAPY: PROTOCOL FOR A FEASIBILITY AND ACCEPTABILITY - Moreira-Gonçalves, Daniel (2022)
Introduction: Prehabilitation is a multimodal strategy implemented in the preoperative period, aiming to increase preoperative functional reserve, leading to better postoperative functional recovery and reduced incidence of complications. The majority of the prehabiliation programs are developed under supervision in an outpatient clinic, which might be an obstacle for those patients with geographical and/or travelling constrains. Home-based programs, with the support of telehealth resources, could be a convenient way to surpass these barriers. Methods: Patients with locally advanced, potentially resectable gastric or GEJ adenocarcinoma, undergoing perioperative chemotherapy with FLOT regimen will be recruited at IPO-Porto and Hospital Garcia de Orta. Patient will be invited to undergo a prehabilitation program (PREHAB) in addition to their usual (medical optimization, nutritional and psychological care). Exercise intervention will comprise aerobic and resistance training. An internet-based platform (iTerapy) via computer or mobile devices, will be used to deliver and monitor the intervention. The primary outcome of this study is to test the acceptability, feasibility and safety of the intervention. As secondary outcomes, we intend to assess the impact of home- based prehabilitation on functional capacity, frailty status, quality of life, disability, postoperative complications and mortality, length of hospital stay, need of ICU, hospital readmission and place of discharge. Conclusion: This study will inform for a future randomized clinical trial to assess the role of prehabilitation to reduce postoperative morbidity and mortality in this population.